Physico-Chemical Assessment of River Benue to Determine Pollution Levels Using Chemometric Models. - UU Egereonu; J.C. Ike; R.U. Iwuagwu; S.K. Egereonu; C. Onwuka; J.C. Egereonu; N.J. Okoro; U.L.Onu; V.C. Eze; B.Okenyi (International Journal of Pollution: Prevention & Control, 2024)
The effects of pollution on water have been reviewed. This study is aimed at determining the level of pollution of the River Benue, with the view of assessing its use as potable water. Different analytical techniques including titrimetry, gravimetry, potentiometry, and spectrophotometry were used for the study. The total hardness gave (22.28 mg/L and 41.87 mg/L) for dry and rainy season respectively. Electrical conductivity gave (91.35 mg/L and 54.10 mg/L) for rainy and dry seasons respectively. The Total dissolved solids gave (76.02 mg/L and 32.31 mg/L) respectively in the rainy and dry season showing the presence of more soluble and dissolved ions in the rainy season. Dissolved oxygen gave (3.18 m/L & 3.72 mg/L) for rainy and dry season respectivley. For phosphate (0.85 mg/L & 0.73 mg/L) were measured in dry and rainy season respectively. Sodium gave (2.95 mg/L & 2.78 mg/L) for dry and rainy seasons. While calcium gave (2.07 mg/L & 1.57 mg/L) for both dry and rainy seasons. While chemical oxygen demand gave (114.37 mg/L &84.97 mg/L) for rainy and dry season. Biochemical oxygen demand were (24.87 mg/L & 25.63 mg/L) for rainy and dry seasons and were above the recommended drinking water standard for world health organization (WHO). Higher level of lead (0.00865 mg/L & 0.00281 mg/L) for both dry and rainy season and copper (1.24 mg/L & 0.9734 mg/L) for both dry and rainy seasons were found in the water which is harmful to health of the aquatic ecosystem and the communities utilizing the water for domestic purposes. The mean values of all the parameters were correlated using Pearson Product Moment Correlation Coefficient. The value of r is 0.91. This implies that the status of the river as it concerns its potability is the same, irrespective of the little fluctuation that might be observed in the different season. MATLAB and ANN were also used for the analysis of River Benue.
Keywords: ANN; MATLAB; Pearson Product Moment; Pollution level; River Benue